GOOD GOVERNANCE: GRANT SERVICE RESEARCH - Rizqia Alfiana; Regina Putri Al Zyahra; Yasmin Afandi; Susi Hardjati (Universitas Halu Oleo, 2021)
Application of Good Governance principle is highly important in the implementation of public services in order to increase the quality of service performance. Social Prosperity Administration Bureau East Java Province as the institution that carries out grant service in their performance is still not going optimal and have to be carried out changes into better ways. This matter is occurred because of application of Good Governance principles that is carried out not maximal by the Social Prosperity Administration Bureau employees in doing services to society agency/institution/organization concerning to grant. This research aims to describe and analyze application of Good Governance principles in carrying out the grant service. This research used Descriptive Qualitative research method based on Good Governance principle according to ((UNDP), 1997) that focus on participation, rule of law, transparency, responsiveness, and accountability. The research value shows that good governance principle has been applied sufficiently optimal in grant service that carried out by Social Prosperity Administration Bureau. It is proven by the existing of the participation applications, service that is carried out under law and applicable SOP (standard Operating Procedure), creating transparency in services, responsiveness and accountability that is given by Social Prosperity Administration Bureau party to receiver grant institution. However, there are also obstacles in this grant service implementation from the application of good governance principle such as human resource that is less mastered on technology and limited employees, lack of time, limited grant budget and lack of awareness of the institution party in collecting the Accountability Sheet.